Chemical Synthesis, Mechanism of Action and Anticancer Potential of Medicinally Important Thiazolidin-2,4-dione Derivatives: A Review - Kumar, Harsh; Deep, Aakash; Marwaha, Rakesh K. (Mini Reviews in Medicinal Chemistry, 2019)
Thiazolidin-2,4-dione (TZD) possessing an active methylene constitute an important chemical class of compounds for the development of new drugs. So, many scholars have synthesized these derivatives as target molecules and evaluated their biological potential. Currently, some of the TZDs are synthesized to treat human cancers stating high levels of PPARγ because it is expected that activation of PPARγ arbitrates their anticancer activity because PPARγ ligands have recently been established to affect differentiation, cell proliferation and apoptosis of different cell types. In the present review, the synthesis of various derivatives of thiazolidine-2,4-diones, their mechanism of action and anticancer activity have been highlighted.
Keywords: chemical synthesis